Pemberdayaan Petani pada Pengolahan Pascapanen Kopi Arabika Proses Full Wash (Coffea arabica L.) di Desa Kalisat Kidul, Kecamatan Kalibening, Kabupaten Banjarnegara: Empowerment of Farmers in Post-Harvest Processing of Arabica Coffee (Coffea arabica L.) in Kalisat Kidul Village, Kalibening District, Banjarnegara (Jurnal Resolusi Konflik, CSR dan Pemberdayaan (CARE), 2023)
Coffee is one of the important export potentials in world trade. Indonesia is classified as the fourth largest coffee exporting country in the world after Brazil, Vietnam and Colombia. (AEKI, 2020). Aceh Province is one of the centers of Gayo Arabica coffee producers in Indonesia. There are three main production areas for gayo arabica coffee, namely the districts of Central Aceh, Bener Meriah and Gayo Lues. Coffee is the main agricultural commodity for the people in the three districts. Post-harvest processing is the second stage after the coffee cultivation process or production management. This stage is important because the final result in post-harvest processing determines the added value or selling value of the harvest. Post-harvest processing is also an important aspect in coffee development. agriculture in Banjarnegara Regency. After harvesting, the next process is post-harvest processing, so that to support good coffee quality is the correct processing. In general, coffee processing can be divided into two, namely wet processing and dry processing. Arabica coffee produced in the Dieng Plateau (Banjarnegara and Pekalongan Districts) is generally processed by wet processing. The processing of coffee beans in Aceh Tengah and Bener Meriah regencies consists of harvesting, peeling fruit skin, fermentation, washing, drying, peeling the skin of coffee beans, sifting (grinding) and polishing. roasting process, manual sorting, warehousing, packaging and packing as well as process control and quality control. The quality of coffee is largely determined by its handling at harvest and post-harvest. So there is a need for empowerment at the farmer level so that farmers are able to produce good quality in the cultivation process.Key words: arabica coffee, empowerment, cherry, postharvest process